Kelp demography and density along the depth gradient monitored at Hansneset, Kongsfjorden, Spitsbergen in 2013 and 2021 - Luisa Düsedau; Stein Fredriksen; Markus Brand; Philipp Fischer; Ulf Karsten; Kai Bischof; Amanda Savoie; Inka Bartsch (PANGAEA, 2024)
Kelp age and density was recorded at Hansneset, Blomstrand in Kongsfjorden, Svalbard, at 2.5, 5, 10 and 15m depth in Summer 2013 and 2021. Our goal was to document changes in Arctic kelp forests dynamics in an Arctic fjord system influenced by glacial melt by repeatedly sampling the same site in a standardized manner. As ocean temperatures in the Arctic have risen substantially and underwater light climate continuously deteriorated over this time period we observed alterations in kelp demography. This data contains results for counts and age measurements of the three dominant kelps at Hansneset, Kongsfjorden, Svalbard: Alaria esculenta, Saccharina latissima, and the Digitate kelps (order Laminariales). Values were calculated by replicates (Replicate) at different water depths (Depth [m]). The number of each species within a given sample were counted (count [#/m^2]) as well as the average age of the specimens in years (mean age [a/m^2]). Note that for the 2013 data, the replicates are given as e.g. R2 because they do not relate to a specific quadrat; whereas for the 2021 data the replicates are given as e.g. Q4 because they relate to the specific quadrat used during that field sampling season. Within the species column there is a extquotesingleDigitate kelps extquotesingle value. This is due to the complication of the visual similarity of Laminaria digitata and Hedophyllum nigripes. Because these are field data, and the distinction between these species requires genetic lab work, the exact species identification is not possible here so the WORMS code is given simply for Laminariales. Historically these kelps were considered Laminaria digitata.